Community education and the older adult - Sidney Lynn Miller; Gladys D. Falconer (Educational Considerations, 1977)
The purpose of this article is twofold: a) to acquaint the reader with some factual information relating to the older American; b) to familiarize the reader with the community education philosophy and based on this philosophy how local communities can plan and implement programs and services for and with older adults.